2016
DOI: 10.2166/wst.2016.235
|View full text |Cite
|
Sign up to set email alerts
|

Modification of waste coal gangue and its application in the removal of Mn2+ from aqueous solution

Abstract: We developed a new calcination method to convert coal gangue (CG), a common waste generated from coal production process, into a modified form, which could be used as an adsorbent to remove Mn(2+) from aqueous solution. Sodium tetraborate (Na2B4O7·10H2O) was added into the CG calcination process as an additive, and the concentrations of Na2B4O7·10H2O were optimized along with the calcination temperature to obtain the best adsorbent capacity of modified coal gangue (MCG). We applied multiple analytical methods … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(12 citation statements)
references
References 28 publications
0
12
0
Order By: Relevance
“…According to Figure 11a, FTIR peaks of Coal Gangue 1-4 were basically the same before and after AMD treatment, indicating that the same coal gangue had the same functional group. The absorption peaks at 1034, 1010, 799 and 466 cm −1 indicated the possible presence of quartz, and 3698, 3650, 1097, 1034, 1010, 799, 687, 533 and 466 cm −1 indicated the possible presence of kaolinite [23]. The absorption peaks at 2920, 2860 and 750-700 cm −1 indicated the presence of organic substances in coal gangue [57].…”
Section: Fourier Transform Infrared Spectroscopy (Ftir) Analysismentioning
confidence: 97%
See 1 more Smart Citation
“…According to Figure 11a, FTIR peaks of Coal Gangue 1-4 were basically the same before and after AMD treatment, indicating that the same coal gangue had the same functional group. The absorption peaks at 1034, 1010, 799 and 466 cm −1 indicated the possible presence of quartz, and 3698, 3650, 1097, 1034, 1010, 799, 687, 533 and 466 cm −1 indicated the possible presence of kaolinite [23]. The absorption peaks at 2920, 2860 and 750-700 cm −1 indicated the presence of organic substances in coal gangue [57].…”
Section: Fourier Transform Infrared Spectroscopy (Ftir) Analysismentioning
confidence: 97%
“…It is found that coal gangue modified by physical or chemical methods can improve its adsorption and can be used for the pre-treatment of industrial wastewater [22]. Ruifang Qiu [23] modified the microstructure of coal gangue by a new calcination method, making coal gangue a low-cost adsorbent that can remove Mn 2+ from industrial wastewater. Preliminary test results show that the spontaneous combustion coal gangue of Gaode coal mine in Fuxin has a certain adsorption effect on Fe and Mn in AMD, and the removal effect is as follows: SRB combined with spontaneous combustion coal gangue > NaOH modified spontaneous combustion coal gangue > unmodified spontaneous combustion coal gangue [24].…”
Section: Of 21mentioning
confidence: 99%
“…23 A low-cost adsorbent for Mn 2+ removal was prepared by adding Na 2 B 4 O 7 •10H 2 O into coal gangue during calcination, and the adsorption capacity went up from 3.2 to 23.9 mg/g. 24 Raw coal gangue powders modified with NaCl, NaOH, and HCl were used to treat Fe 2+ and Mn 2+ in acid wastewater and the coal gangue modified by NaOH showed the best adsorption capacity, that is, 0.811 and 0.321 mg/g for Fe 2+ and Mn 2+ . 25 Although some studies about the adsorption properties of coal gangue have been reported, there still exit a few questions: (a) the coal gangue treated with simple methods is usually grinded by manual operation in small numbers with uneven properties and poor adsorption capacity, (b) chemical modification for coal gangue or using coal gangue as starting material to synthesis zeolite is complicated and costly, which limits its practical application in industrial production.…”
Section: Introductionmentioning
confidence: 99%
“…Coal gangue was combined with biomass to prepare biochar for phosphate removal; the adsorption capacity of the prepared biochar could reach to 3.196 mg/g 23 . A low‐cost adsorbent for Mn 2+ removal was prepared by adding Na 2 B 4 O 7 ·10H 2 O into coal gangue during calcination, and the adsorption capacity went up from 3.2 to 23.9 mg/g 24 . Raw coal gangue powders modified with NaCl, NaOH, and HCl were used to treat Fe 2+ and Mn 2+ in acid wastewater and the coal gangue modified by NaOH showed the best adsorption capacity, that is, 0.811 and 0.321 mg/g for Fe 2+ and Mn 2+ 25 .…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, many investigations have focused on its promising adsorption property in polluted water, especially for heavy ions and organic dyes [21][22][23][24]. Qiu and Cheng [21] modified the coal gangue with sodium tetraborate (Na 2 B 4 O 7 ·10H 2 O) during calcination process to improve its removal efficiency of Mn 2+ , which was due to the increase of pore volume (from 0.021 to 0.067 cm 3 /g) and specific surface area (from 9.29 to 20.05 m 2 /g) for raw coal gangue. The decomposition of carbonate minerals and dehydration of coal gangue particles by addition of sodium tetraborate during calcination were originated from the generation of porous structure and large specific surface area.…”
Section: Introduction mentioning
confidence: 99%